2014
DOI: 10.1016/j.bbcan.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin, DNA torsion, and chromatin dynamics

Abstract: Doxorubicin is one of the most important anti-cancer chemotherapeutic drugs, being widely used for the treatment of solid tumors and acute leukemias. The action of doxorubicin and other anthracycline drugs has been intensively investigated during the last several decades, but the mechanisms that have been proposed for cell killing remain disparate and controversial. In this review, we examine the proposed models for doxorubicin action from the perspective of the chromatin landscape, which is altered in many ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
455
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(503 citation statements)
references
References 76 publications
9
455
0
13
Order By: Relevance
“…A statistical functional analysis of these nonsynonymous variants using Web-based Gene Set Analysis Toolkit (WebGestalt) (13) showed that three representative terms were enriched in the Gene Ontology (GO) molecular function category, namely "carbohydrate derivative binding," "nucleoside binding," and "ATP-dependent helicase activity" (SI Appendix, Table S2). These findings further support the findings of previous studies that DOX inhibits the enzyme topoisomerase II by intercalating between two base pairs of the DNA double helix (14).…”
Section: Resultssupporting
confidence: 92%
“…A statistical functional analysis of these nonsynonymous variants using Web-based Gene Set Analysis Toolkit (WebGestalt) (13) showed that three representative terms were enriched in the Gene Ontology (GO) molecular function category, namely "carbohydrate derivative binding," "nucleoside binding," and "ATP-dependent helicase activity" (SI Appendix, Table S2). These findings further support the findings of previous studies that DOX inhibits the enzyme topoisomerase II by intercalating between two base pairs of the DNA double helix (14).…”
Section: Resultssupporting
confidence: 92%
“…4 Doxorubicin has different modes of action such as topoisomerase II poisoning, DNA adduct formation, oxidative stress, histones eviction, and ceramide overproduction. 5 Contrary to its high activity against SCLC, it is relatively ineffective against NSCLC. Even in SCLC, doxorubicin-based chemotherapy regimens frequently fail due to inherent and acquired resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubcin (DOX), also known as adriamycin, is widely used as an anti-tumor drug. Its mechanisms of action include the induction of apoptosis of tumor cells by intercalating into their DNA to inhibit its transcription and initiate a DNA damage response (5). DOX-based chemotherapy is used against a wide range of cancer types, including ovarian (6), breast (7) and bladder cancer (8) as well as HCC (9).…”
Section: Introductionmentioning
confidence: 99%